Revitalization Of Aceh Customs in Formal Educational Institutions - Sri Suyanta (Ar-Raniry: International Journal of Islamic Studies, 2016)
The study aims to strengthen the role of school in transforming Acehcustoms. Schools as an official formal education institution, dealing with twoissues namely their feelings cannot be ignored between customs and culture is acase that should be maintained continuously, and schools have to collide withsystem reining the power of cruising and creativity of education institutions indeveloping the value of custom. In addition, schools have a desire to interpretAceh customary by themselves. Those things are done in two issues; First, thelack of teacher understanding customs well and perfectly. Secondly, lowsupported funding supporting every work in revitalization of custom. The studyfound that revitalization and strategy in developing in formal schools areundergone by two ways; theory and practice. Theoretically, schools includecustom materials through several lessons. Then practically, schools encouragestudents’ creativity in many ways, both in school activities internally andexternally